Barberoda: Innovating grooming experiences with mobile convenience / Ahmad Fikri Hanis Zulhisham ... [et al.] - Zulhisham, Ahmad Fikri Hanis; Syamsyul Ariffin, Muhammad Azeem; Muhamad Roshidi, Muhammad Amir Nursharifudin; Sarifudin, Nur Safura; Baharom, Shahrel Nizar (2024)
In an age emphasizing convenience and tailored experiences, BarbeRoda presents an innovative solution to the inefficiencies inherent in conventional barber services. BarbeRoda aligns its operations with the ethos of innovation and accessibility. Central to its vision is the deployment of a Mobile Barber Vehicle, leveraging technology to revolutionize grooming experiences. A user-friendly mobile app facilitates seamless booking, payment, and service selection, catering to the needs of professionals, students, travelers, and the elderly, eliminating the inconvenience of physical travel and waiting times associated with traditional barbershops. This novel approach brings personalized grooming services directly to the customer's doorstep, emphasizing quality, affordability, and customer satisfaction. BarbeRoda's innovative strategy positions them as pioneers in mobility solutions, challenging existing market norms and setting new standards in the grooming industry. By integrating entrepreneurship with social science, BarbeRoda not only seeks to attract investment, but also aims to redefine grooming standards, promising a transformative impact on the market.